PROSPECTS FOR IMPLEMENTATION OF LEARNER-CENTERED ENGLISH LANGUAGE TEACHING AT TECHNICAL UNIVERSITIES - Podorozhna , A. (Problems of Engineer-Pedagogical Education, 2023)
The article reveals the concept of learner-centered learning; on the basis of the analysis of scientific and pedagogical literature the characteristic features of learner-centered learning of English in technical universities have been identified, namely the emphasis on active rather than passive English learning, focus on advanced studying and understanding, students’ increased responsibility and accountability, interdependence between the teacher and the student, mutual respect in the relationship between the instructor and the learner, reflective approach to the learning process on the side of both the teacher and the student, and possibility for the student to develop an independent learning trajectory, "a route map", especially in senior courses. The author emphasizes that the main goal of the learner-centered approach to teaching English in higher technical education institutions is to organize such a learning environment in which the students themselves will be able to determine the vector of their foreign language learning. The paper determines the technology of teaching English at technical universities to organize effective learner-centered learning: practice-oriented content-centered learning of English, and process-oriented learning content. The author analyzes the advantages and difficulties of applying student-centered pedagogical strategies in the process of teaching English in higher technical education institutions, and concludes that the student-centered approach in the process of teaching English in higher technical education institutions is not fully used today; this is primarily due to difficulties of both organizational and psychological nature. Lack of motivation to learn a foreign language on the side of students is one of the main factors hindering the implementation of the above-mentioned approach; lack of awareness of teachers and students about the benefits of student-centered approach; difficulties associated with the whole traditional pedagogical system, such as assessment and rigid curriculum, and a large number of students in the group – all this also creates serious obstacles to real progress in student-centered learning of the English language in a technical university.